2018
DOI: 10.3390/cancers10010026
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancers: An Update on Their Molecular Pathology

Abstract: Colorectal cancers (CRCs) are the third leading cause of cancer-related mortality worldwide. Rather than being a single, uniform disease type, accumulating evidence suggests that CRCs comprise a group of molecularly heterogeneous diseases that are characterized by a range of genomic and epigenomic alterations. This heterogeneity slows the development of molecular-targeted therapy as a form of precision medicine. Recent data regarding comprehensive molecular characterizations and molecular pathological examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
114
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(117 citation statements)
references
References 126 publications
1
114
0
2
Order By: Relevance
“…EMT progression involves the localized occurrence of a loss of epithelial differentiation and the acquisition of a mesenchymal phenotype. This process enhances the motility and invasion of cancer cells and plays an important part in the consensus molecular subtype (CMS) classifications . CRCs with EMT signature are classified into CMS4 subgroup (an EMT‐related subtype), characterized as more aggressive phenotype showing poorer overall survival and signatures of high TGF‐β signaling and EMT activation .…”
Section: Discussionmentioning
confidence: 99%
“…EMT progression involves the localized occurrence of a loss of epithelial differentiation and the acquisition of a mesenchymal phenotype. This process enhances the motility and invasion of cancer cells and plays an important part in the consensus molecular subtype (CMS) classifications . CRCs with EMT signature are classified into CMS4 subgroup (an EMT‐related subtype), characterized as more aggressive phenotype showing poorer overall survival and signatures of high TGF‐β signaling and EMT activation .…”
Section: Discussionmentioning
confidence: 99%
“…Besides , among cancer-related mortality, the third most common cause of death was due to the CRC (Inamura, 2018). According to the statics of 2008, the estimation regarding the incidence and mortality of CRC showed that, approximately 50,000 death among the whole of 150,000 diagnosed cases (László, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is a neoplastic condition of great medical and social interest, and despite the considerable progress achieved in the comprehension of its molecular pathogenesis, it remains the most frequent tumor in general population and the second cause of cancer-related death in Western countries [1]. The development of CRC is a multistep process in which a series of genetic and epigenetic alterations activates proto-oncogenes and inactivates oncosuppressor genes, leading to the malignant transformation of colorectal mucosa cells [2,3]. The initial, and probably most important, among such modifications determines a constitutive activation of the βcatenin signaling pathway, resulting in an increased proliferation of CRC cells.…”
Section: Introductionmentioning
confidence: 99%